CITRA PERUSAHAAN DAN TINGKAT KEPUASAN PELANGGAN SUTAN RAJA HOTEL AND CONVENTION PALU - Lethicia, Anita (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2018)
This study aims to determine the relationship between company image and the level of customer satisfaction at Sutan Raja And Convention Hotel Palu. In this study, the company's image is measured by: the impression, trust and attitude of the customer. While the level of customer satisfaction is measured from: Re-Purchase, Creating Word-of-Mouth, Creating Brand Image, and Creating Purchasing Decisions on the Same Company. The type of research used is explanatory type. The sampling technique uses the Accidental Sampling method with 60 respondents. The data collection tool uses a questionnaire. The data analysis technique uses multiple correlation as the basis for decision making in the research hypothesis test. The results of the study show that there is a relationship between the company's image and the level of customer satisfaction as evidenced by the results of multiple correlation analysis which indicates a very strong relationship. Where the R value is 0.845> from the Rtable value of 0.254 at a significant level of 5%. Thus the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted which means that there is a significant relationship between the company's image and the level of customer satisfaction at Sutan Raja Hotel And Convention Palu.